Annam Mata cha Brahma Remembering Amma(mother) Through the Kongu Food Culture: In Conversation with Author Perumal Murugan - Vinai, Maya; Ahmed Shabin, (SARE: Southeast Asian Review of English, 2023)
Perumal Murugan is an acclaimed Indian novelist, essayist and poet who writes in Tamil language. He has been hailed by audiences and connoisseurs alike for his excellent storytelling, attention to detail and representation of the brutal realities of the rural agrarian communities of Kongu Nadu Despite the whirlpool of controversies and threats that surrounded Murugan’s life and writings, nothing has deluded him from the path of being a committed writer determined to use writing as a weapon to expose the societal inconsistencies. The present interview revolves around the role of food in his creative works. It includes a discussion of the various culinary traditions and food paradigms of his ancestral village, the reverence for food and environment amongst agrarian communities, the difference that food preferences create amongst people, and the entry of the fast-food culture due to globalization. Along with his other literary works, the interview also briefly discusses his memoir Amma, where Murugan recollects the cherished food memories of his childhood and also of his mother whose values and love for cooking have shaped both his identity and culinary preferences. Murugan’s penning or narrativizing of these memories through various creative forums has assisted in what David Sutton calls as “prospective memory” (163) aiding the process of how people plan to remember meals and how tasty they would be. Keywords: Culinary fiction, Kongu cuisine, Pongal, community, memory